Modelos agrícolas para aumentar a eficiência produtiva nos sistemas de produção de grãos em ambientes subtropicais - Tagliapietra, Eduardo Lago (2024)
Studies on yield gaps in individual crops to identify the possibility of increasing yield are frequent in the literature. However, annual yield can also be increased by altering the type, number, and temporal arrangement of individual cropping cycles within the cropping sequence. The expansion of the soybean sowing period, motivated by the search for greater yield potential and efficiencies in the production system, results in the difficulty for the classification system of relative maturity groups to capture the genotype x environment interaction satisfactorily for environments subtropics. The objectives of this study were: (l) quantify the potential and energy gap per unit area and time of the main production systems in South of Brazil and (ll) develop a system for indicating soybean cultivars based on the optimal agronomic cycle of each GMR for the South of Brazil, aiming to increase the productive efficiency of the crop. The main production systems in the South of Brazil were identified and estimated for water-limited energy potential and energy gaps, which were calculated using agricultural models over 16 years. The estimates considered the management practices representative of each region. The adjustment in the estimation of maturation groups followed the methodology described by Alliprandini et al. (2009), and the optimal agronomic cycle for different GMRs and sowing times was estimated using the limit function proposed by French and Schultz (1984). Adopting production systems increases the energy yield of cultivated land in the South of Brazil, reducing production risks and serving as a form of income diversification for farmers. The use of more intensive systems can result in 151 and 87 GJ ha-1 year-1 (CSYgAi) more annual energy production in the PR and RSC regions, respectively, while reducing the energy gap in individual crops in 50 and 41 GJ ha-1 year-1. Knowing the duration of the crop development cycle at different sowing times, combined with the optimal agronomic cycle, made it possible to optimize the positioning of cultivars, increasing crop yield. An average increase of 8% in yield can be achieved using the Best Cultivar software to better position cultivars at sowing times, thus maximizing the genotype x environment interaction.